2022
DOI: 10.1097/psy.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cold Exposure Training and a Breathing Exercise on the Inflammatory Response in Humans: A Pilot Study

Abstract: ObjectiveWe previously showed that a training intervention comprising a combination of meditation, exposure to cold, and breathing exercises enables voluntary activation of the sympathetic nervous system, reflected by profoundly increased plasma epinephrine levels, and subsequent attenuation of the lipopolysaccharide (LPS)-induced inflammatory response. Several elements of the intervention may contribute to these effects, namely, two different breathing exercises (either with or without prolonged breath retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(101 citation statements)
references
References 26 publications
2
59
0
1
Order By: Relevance
“…Studies have found anti-inflammatory impacts (Buijze et al, 2019 ; Zwaag et al, 2020 ), control over autonomic parts of the nervous system (Kox et al, 2012 , 2014 ; Muzik et al, 2018 ), resistance to endotoxins (van Middendorp et al, 2016 ), and accelerated acclimatization to high altitudes (Buijze & Hopman, 2014 ). Consistent with the WHM’s notion of three integrated pillars, empirical evidence shows that the main techniques of breathing exercises and cold exposure may yield unique physiological effects (Zwaag et al, 2022 ). Hence, it may be expected that their combined application leads to an interaction and thus, greater effects than a total of the two isolated techniques would suggest.…”
Section: Related Workmentioning
confidence: 88%
See 4 more Smart Citations
“…Studies have found anti-inflammatory impacts (Buijze et al, 2019 ; Zwaag et al, 2020 ), control over autonomic parts of the nervous system (Kox et al, 2012 , 2014 ; Muzik et al, 2018 ), resistance to endotoxins (van Middendorp et al, 2016 ), and accelerated acclimatization to high altitudes (Buijze & Hopman, 2014 ). Consistent with the WHM’s notion of three integrated pillars, empirical evidence shows that the main techniques of breathing exercises and cold exposure may yield unique physiological effects (Zwaag et al, 2022 ). Hence, it may be expected that their combined application leads to an interaction and thus, greater effects than a total of the two isolated techniques would suggest.…”
Section: Related Workmentioning
confidence: 88%
“…Research has examined the potential of mindfulness-related techniques such as yoga, particularly the influence of yogic breathing, i.e., pranayama (Cowen, 2010 ; Kanchibhotla et al, 2021 ; Lei Chui et al, 2021 ). Extant findings show that these exercises can improve markers that are symptomatic for perceived stress, such as inflammatory mediators (Kox et al, 2014 ; Zwaag et al, 2022 ). An important concept in research on physiological stress countermeasures, explaining their mechanisms of action, is that of hormesis.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations